(untitled) (Journal of Pathology of Nepal, 2020)
Background: The similarity in clinical presentations of a wide gamut of non-neoplastic cutaneous pathology leads to diagnostic challenges. Histopathological study of skin biopsy aids in the accurate identification of skin lesions so that they can be managed appropriately. Materials and Methods: A retrospective descriptive study was performed in the Department of Pathology at Patan Academy of Health Sciences from April 2017 to March 2020. Data from the histopathology database were analyzed using SPSS version 17.0. Results: Non-neoplastic lesions constituted 180 cases (31.86%) of the total of 565 skin biopsies received during the study period. The age ranged from 5 months to 95 years with a mean age of 36 years. There was no overall particular gender predilection. Amongst the diagnostic categories, the prevalence of non-infectious erythematous, papular, and squamous diseases was the highest followed by microbial diseases and non-infectious vesiculobullous and vesiculopustular diseases. Lichen planus followed by urticaria was the most frequently encountered lesions in non-infectious erythematous, papular, and squamous diseases. Leprosy was the commonest microbial disease. In the non-infectious vesiculobullous and vesiculopustular category, spongiotic dermatitis was most prevalent. Spongiotic dermatitis followed by lichen planus, leprosy, and calcinosis cutis were the commonest non-neoplastic disorders. Conclusions: Amongst the diagnostic categories, the prevalence of non-infectious erythematous, papular, and squamous diseases was the highest followed by microbial diseases and non-infectious vesiculobullous and vesiculopustular diseases. In this study, spongiotic